Abdullah Bin Saba': Analisis dari Perspektif Cendekiawan Islam - Yusof, Abdullah (Jurnal Usuluddin, 2001)
This article tries to discuss the role of Abdullah bin Saba', one of the legendary heroes of the Muslim community of the preliminary-Islamic History. The discussion is mainly based on Muslim scholars' perspectives. His role is also viewed by some orientalists as well as Muslim scholars through their arguments. The main aim of this article is to have an overview of several important events which were related to Abdullah bin Saba' as recorded by Muslim historians in their classical books.